2009
DOI: 10.1159/000207526
|View full text |Cite
|
Sign up to set email alerts
|

A complex medical phenotype in a patient with triplication of 2q12.3 to 2q13 characterized with oligonucleotide array CGH

Abstract: We report an adult female with a left polycystic kidney, patent ductus arteriosus, left streak ovary, bicornuate uterus and deafness who presented with infertility. She has an intrachromosomal triplication of bands 2q12.3 to 2q13, with inversion of the central segment, which arose de novo from a paternal interchomosomal event. The triplication contains 68 known genes within the 7.28 Mb of DNA between base pairs 107,140,721 and 114,416,131. All intrachromosomal triplications are rare and, while partial duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In three of the cases, where the parent of origin could be determined, the inverted triplication was found to be composed of alleles from both homologs of one of the parents in a 2∶1 ratio, consistent with the hypothesis that the event occurred in a meiotic or a pre-meiotic division [8], [14], [15]. In all cases of de novo triplications with an inverted central copy, the distal portion of the chromosome was retained.…”
Section: A Unique Class Of Genomic Rearrangementssupporting
confidence: 75%
“…In three of the cases, where the parent of origin could be determined, the inverted triplication was found to be composed of alleles from both homologs of one of the parents in a 2∶1 ratio, consistent with the hypothesis that the event occurred in a meiotic or a pre-meiotic division [8], [14], [15]. In all cases of de novo triplications with an inverted central copy, the distal portion of the chromosome was retained.…”
Section: A Unique Class Of Genomic Rearrangementssupporting
confidence: 75%
“…Most of the reported cases of intrachromosomal triplication had inversion of the middle repeat and in all cases, except one, the parental chromosomes were normal. The parental origin of most reported triplications is maternal, but cases with paternal origin have been described [Ungaro et al, 2001; Schluth et al, 2005; Mercer et al, 2009]. In most cases, both alleles are involved in the rearrangement, pointing to meiosis I as the site of the rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent maternal [Schinzel et al, 1994; Long et al, 1998; Roberts et al, 2002; Vialard et al, 2003] and paternal [Ungaro et al, 2001; Schluth et al, 2005] interstitial triplications of 15q11–q13 account for the majority of reported patients. Sporadic triplications of 2q11.2–q21 [Wang et al, 1999], 2q12.3–q13 [Mercer et al, 2009], 2q37 [Rauch et al, 1996], 3q25.3–q29 [Ounap et al, 2005], 5p14–p15.33 [Harrison et al, 1998], 7p21.3–p22 [Rivera et al, 1998], 12p11.2–p12.3 [Eckel et al, 2006] have also been reported. Because of their rarity, a detailed molecular characterization, necessary to define the mechanism of their formation, has so far been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetically invisible tetrasomy due to a chromosome segment microtriplication is a very complex and rare CNV. Till date, only a few triplications have been reported, including 2q11.2 → q21 [ 11 ], 2q12.3 → q13 [ 12 ], 3q25.3 → q29 [ 13 ], 7q11.23 [ 14 ], 13q14 [ 15 ], 15q11 → q13 [ 16 ], 17p11.2 → p12 [ 17 ] and 22q11.2 [ 18 ]. A case of “pure” 1p36 tetrasomy has not yet been reported, although complex rearrangements resulting in deletions, duplications and/or triplications for portions of 1p36 have been reported elsewhere, along with postulated mechanisms of formation [ 19 , 20 ].…”
Section: Case Presentationmentioning
confidence: 99%